Oświecenie raz jeszcze - Link-Lenczowski, Andrzej K. (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
The Author is trying to explain the “English” or “British” background of the Enlightenment by showing two main elements of the first shape of Pre-Enlightenment attitudes in the 17th century. Most important were the tracts of the Calvinists and radical nonconformists (Puritans). They stressed importance of the human-free will and experiment in opposition to the God’s intervention in the history of the mankind.